1988
DOI: 10.1021/es00171a013
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and mobility of selenium and other trace elements in shallow groundwater of the western San Joaquin Valley, California

Abstract: rn Samples of shallow groundwater that underlies much of the irrigated area in the western San Joaquin Valley, CA, were analyzed for various major ions and trace elements, including selenium. Concentrations of the major ions generally were similar for groundwater collected in the two primary geologic zones-the alluvial fan and basin trough. Selenium concentrations are significantly (a = 0.05) higher in the groundwater of the alluvial-fan zone than in that of the basin-trough zone. The concentrations of oxyanio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 10 publications
3
45
0
1
Order By: Relevance
“…In both freshwater phytoplanktonic and marine algae communities, SeO4 2-is considered to be more ecologically toxic than SeO3 2-. 28,29 In most WSJV soils, Se is predominately present as SeO4 2-, and less abundant SeO3 2-, due to irrigation water leaching out local SeO4 2--enriched alluvial fan derived soils 2,30 (see Supporting Information Figure 1). The RRR agricultural drainage waters also have high sulfate concentrations of up to 100 g L -1 and nitrate concentrations of up to 300 mg L -1 .…”
Section: Selenium Water Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In both freshwater phytoplanktonic and marine algae communities, SeO4 2-is considered to be more ecologically toxic than SeO3 2-. 28,29 In most WSJV soils, Se is predominately present as SeO4 2-, and less abundant SeO3 2-, due to irrigation water leaching out local SeO4 2--enriched alluvial fan derived soils 2,30 (see Supporting Information Figure 1). The RRR agricultural drainage waters also have high sulfate concentrations of up to 100 g L -1 and nitrate concentrations of up to 300 mg L -1 .…”
Section: Selenium Water Chemistrymentioning
confidence: 99%
“…In Se polluted aquatic environments, such as Kesterson Wildlife Reservoir in WSJV, Se is present primarily as watersoluble selenate (SeO4 2-) ≥ 98% and ∼2% selenite (SeO3 2-). 2 Due to its relative abundance in these environments, ecotoxicity concerns center around SeO4 2-and its biomagnification up the aquatic food chain. 10,11 Selenium evapoconcentration in aquatic ecosystems has been documented to cause deformity and mortality in fish, waterfowl, shore birds, and mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Sources of dissolved selenium in ground and surface water in the San Joaquin Valley were hypothesized to be sulfides in shale (the Moreno Formation of Cretaceous age) of the Coast Range of California (Presser and others, 1990) and sediments of the west-central San Joaquin Valley derived from Coast Range rocks (Deverel and others, 1984;Gilliom, 1989;Izbicki, 1989). Studies by Deverel and Millard (1988) and by Fujii and Deverel (1989) concluded that high concentrations of selenium in ground and surface water were a result of evaporative concentration of ground water, which was indicated by isotopic enrichment of oxygen and hydrogen stable isotopes and by correlation of elevated selenium concentrations with ground-water salinity. The hydrogeochemical processes involved in the immobilization of selenium from the aqueous phase has been the focus of several studies (Dubrovsky and others, 1990;Masscheleyn and others, 1991;Sposito and others, 1991;White and others, 1991).…”
Section: Ground-water Investigations 33mentioning
confidence: 99%
“…In aqueous environments Se forms selenide (Se ), which are often associated with iron oxides. The concentration of each Se species depends on the local redox environment [14]. Selenate adsorbs less strongly than selenite and is therefore considered the predominant species susceptible to biotransformation in the environment [15].…”
Section: Introductionmentioning
confidence: 99%